Intracellular trafficking and cytotoxicity of a gelatine-doxorubicin conjugate in two breast cancer cell lines - Alvi, Mohammed M.; Nicoletto, Rachel E.; Eshmawi, Bayan A.; Kim, Hyun (Kate); Cammarata, Christopher R.; Ofner, Clyde M. (Journal of drug targeting, 2020)
Details of intracellular pathways of cytotoxicity remain unclear for doxorubicin conjugates being studied to treat breast cancer tumours. A high molecular weight gelatine-doxorubicin conjugate was investigated with an emphasis on lysosome participation. The conjugate was synthesised and characterised. Cell uptake and cellular localisation in MCF-7 and triple negative breast cancer (TNBC) MDA-MB-231 cells were determined with fluorescence microscopy. Nuclear content of released DOX was determined by UHPLC. Cytotoxicity was determined by the MTT assay. Lysosome membrane permeabilization (LMP) was followed by lysosomal release of fluorescently labelled dextran. After incubation at an equivalent 10 µM DOX, conjugate lysosome accumulation was substantial in both cell lines by 24 h, at which time the conjugate cytotoxic effect was first observed. By 48 h, the conjugate was nearly fourfold more toxic in TNBC than in MCF-7 cells. The MCF-7 nucleus drug content from conjugate released DOX was small but confirmed intra-lysosomal drug release. The conjugate induced LMP in 100% of TNBC cells but LMP was virtually absent in MCF-7 cells. These results suggest that the conjugate induces cytotoxicity by a lysosomal pathway in MDA-MB-231 cells and has potential for treatment of TNBC tumours. Support: NIH/NCI R15CA135421, the Agnes Varis Trust for Women's Health.